A LINGUAGEM RELIGIOSA DO HINÁRIO SIVAYI SUKU DA IESA - IGREJA EVANGÉLICA SINODAL DE ANGOLA NO POVO DOS OVIMBUNDU COMO DOCUMENTO DO “ENTRE-LUGAR” DO CRISTIANISMO E DA CULTURA TRADICIONAL BANTU - ESTENDAR, JÚLIO MACUVA (2020)
The present work focuses on an aspect of the Christological language of Christianity of the Angolan Ovimbundu peoples, particularly on the Evangelical Synodal Church of Angola (ESCA) community faith. The processes of interaction and negotiation between Western Christianity and the traditional culture / religiosity of Bantu communities in sub-Saharan Africa are investigated, through their preservation in the religious language of ESCA, established by that church through its hymnbook, called Sivayi Suku (praise God). The hymnbook is a bilingual religious document that contains hymns in Portuguese and Umbundu. Based on the translational processes of these hymns, we seek to interpret and understand the particularities and creativity of their religious language. As a theoretical reference, we started from Homi Bhabha to glimpse and understand the splits and disjunctions, as well as the symbolic, cultural and linguistic negotiations that took place at the cultural / religious borders and between-places between the two interlocutors involved in the inter / intercultural dialogue. We concluded that ESCA and its hymnbook are the result of a process of negotiating the Christian theology / culture of the missionaries and the culture / religiosity of the Ovimbundu.